Comparative Study between Ethanolic and β-Cyclodextrin Assisted Extraction of Polyphenols from Peach Pomace. (8th March 2018) - El Darra, Nada; Rajha, Hiba N.; Debs, Espérance; Saleh, Fatima; El-Ghazzawi, Iman; Louka, Nicolas; Maroun, Richard G.
Abstract : Peach byproducts are often regarded as food waste despite their high content in health-promoting components. Amongst the latter, polyphenols are bioactive molecules with significant health benefits. The present study investigated an eco-friendly and cost-effective method using a GRAS food additive, β -cyclodextrin ( β -CD), for the recovery of polyphenols from peach pomace. β -CD assisted extraction of polyphenols was compared to that of conventional solvent (ethanol) extraction at the same concentrations (10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, and 50 mg/mL) in terms of quality (antiradical activity) and quantity. The extract obtained by 50 mg/mL β -CD assisted extraction showed the highest polyphenol (0.72 mg GAE/g DM) and flavonoid (0.35 mg catechin/g of DM) concentrations as maximal antiradical activity (6.82%) and a noted antibacterial activity. Our results showed the competitiveness of β -CD assisted extraction to recover a high quantity and quality of polyphenols from peach pomace suggesting β -CD as a green alternative method for phenolic extraction.